CHARACTERISTICS OF PREGNANT WOMEN WITH THE CHRONIC ENERGY DEFICIENCY AT THE PHC OF PASUNDAN GARUT - Rohiman .; Imas Rafiyah; Sukmawati . (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2019)
In 2016, community health center of Pasundan Garut was the first rank in terms of the total number of chronic deficiency energy for pregnant women in Garut. The characteristics of pregnant women with chronic energy deficiency (abbreviated as CED) are not definitely identified. This research is aimed to identify the characteristics of pregnant women with CED. This descriptive research used quantitative approach. The population of this study was 61 pregnant women with CED and the whole population was taken as samples. The research instrument was developed from the Child Identity Card book and the data was collected by using interview and documentation study. The result of the documentation study showed that most pregnant women with CED were at not risk age (62.3%), not educated women (59%), unemployed women (68.9%), at not risk parity (98.4%), birth spacing ≥ years (54.1%), no pregnant complication found (78.7%), no history of infectious diseases and allergies (85.2%), consuming Fe tablets (68.9%). The data collected through interview revealed that the respondents had low income (85.2%) and no diverse diet (59%) because they hardly to consume fruits, ate lack portion, had dietary restrictions and processed the food with the wrong manner. This research concludes that the main cause of CED in the community health center of Pasundan Garut is generally described based on the characteristics of family income and dietary pattern. Therefore, it is considered necessary to do counseling and guidelines to exploit and take full advantage of potential such as a vertical garden for self-sufficiency.Keywords: Chronic Energy Deficiency, Characteristic, Pregnant Women.